From Ethnocultural Knowledge to Systems Thinking: Mapping Global Research on Ethno-ESD in Elementary Education - Mulyadiprana, Ahmad; Hamdu, Ghullam; Merliana, Anggit; Mulyati, Srie; Yulianto, Ade; Hamzah, Rifqy Muhammad (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to analyze global research trends, thematic evolution, and research characteristics related to Ethno-ESD and systems thinking in elementary education using a bibliometric approach. The study employed bibliometric analysis using Biblioshiny within the Bibliometrix package in RStudio. A total of 44 documents published between 2017 and 2026 were retrieved from the Scopus database and analyzed, representing 33 sources. The analysis focused on publication trends, authorship patterns, citation metrics, and thematic mapping based on keyword co-occurrence. Thematic analysis was conducted to identify and interpret recurring themes and patterns across research topics and keywords. The findings revealed an annual growth rate of 8.01%, indicating increasing scholarly interest in the topic. The dominant motor themes were sustainable development, education, and learning, suggesting that sustainability-oriented educational practices remain central to current research. The collaboration index indicated a moderate level of international research collaboration. These findings suggest that research on Ethno-ESD and systems thinking in elementary education is evolving toward interdisciplinary and sustainability-focused learning approaches. This study contributes to the identification of future research directions and provides a scientific basis for integrating local wisdom and systems thinking into sustainable elementary education practices.